CODE-MIXING IN SELECTED EPISODES ON BOY WILLIAM'S YOUTUBE CHANNEL - Nuraeni, Cicih (IKIP Siliwangi, 2022)
This research is used descriptive qualitative method which aims to identify the types and the dominant used of code-mixing in selected episodes on Boy William YouTube channel. The data collected from the dialogues in 3 (three) episodes then identified and classified into types of code-mixing based on the theory of Hoffman (1991). Based on Hoffman (1991) there 3 (three) types of code-mixing, they are intra sentential, intra lexical and involving a change of pronunciation. The result showed that there are 61 intra sentential code-mixing (78%), 9 intra lexical (9%) and 8 involving a change of pronunciation (8%). So, it can be concluded that dominant code-mixing in 3 (three) episodes on Boy William YouTube Channel is intrasentential. Keywords: Code-Mixing, Linguistics, Sociolinguistics, Youtube